Second scuttled ship of Trstenik, Kaštel Sućurac, Croatia; Preliminary report - Ruff, David G. (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
In 2020, during the research of a scuttled Roman ship at Trstenik in Kaštel Sućurac, two more scuttled ships were discovered on its western and eastern sides. All the ships were filled with large rocks, and scuttled in order to reinforce the operational waterfront of the economic complex (villa rustica), which existed from the end of the Late Roman Republican to the Late Imperial period. In 2021, the westernmost ship, called Trstenik 2, whose total length slightly exceeded 5 m, was fully explored. It is a specific type of vessel, characterized probably by a bow transom, in ancient sources called horeia.